The Value of Islamic Education in the Pharmacist Profession in Pharmaceutical Services (Study at the Bandar Khalipah Community Health Centre, Deli Serdang Regency) - Fauzi, Ahmad; Lubis, Indah Suci Kesuma (ISTIFHAM, 2025)
Pharmaceutical services in Indonesia play a key role in supporting public health, especially at the primary care level, such as community health centres. Among Muslim communities, these services are not only focused on medical and technical aspects but also serve as a medium for da’wah by integrating Islamic educational values. This study aims to explore the role of Muslim pharmacists at the Bandar Khalipah Community Health Centre in Deli Serdang Regency in incorporating da’wah messages, such as patience, discipline, sincerity, and avoidance of wastefulness, into interactions with Muslim patients during pharmaceutical practice. The research used a qualitative case study approach, including observation, in-depth interviews, and documentation, supported by thematic analysis to identify key patterns in service practices. The findings show that pharmacists and pharmacy assistants regularly incorporate Islamic prophetic values in patient interactions, both through direct communication and spiritual practices such as prayer and reciting basmallah during medication preparation. Muslim patients reported receiving more holistic care that addresses both medical and spiritual needs, which helped improve adherence to treatment and psychological comfort. This study contributes by reinforcing the integration of Islamic educational values into the pharmacy profession and by expanding the literature on Islamic pharmacy and Sharia-based biomedical ethics. The implications highlight the need for developing pharmaceutical service policies that are sensitive to religious and cultural values, as well as fostering further research on how integrating Islamic values impacts healthcare quality in various settings.